2011
DOI: 10.4103/0970-9185.81842
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative analgesia in children when using clonidine or fentanyl with ropivacaine given caudally

Abstract: Background:The aim of the study was to compare the efficacy of clonidine and fentanyl as an additive to ropivacaine given via single shot caudal epidural in pediatric patients for postoperative pain relief.Materials and Methods:In the present double blind study, 90 children of ASA-I-II aged 3-8 years scheduled for infraumblical surgical procedures were randomly allocated to two groups to receive either ropivacaine 0.25% 1 ml/kg + clonidine 2 μg/kg (group I) or ropivacaine 0.25% 1 μl/kg + fentanyl 1 μg/kg (grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 30 publications
(47 reference statements)
4
39
0
1
Order By: Relevance
“…One study that compared the efficacy of IV clonidine or fentanyl in conjunction with ropivacaine given caudally for postoperative pain relief resulted in no significant difference in oxygen saturation (Spo 2 ) (p>0.05). 17 An RCT studied caudal blockade with single dose clonidine, hydromorphone, or morphine combined with ropivacaine with epinephrine in children undergoing ureteral implantation. 18 No postoperative respiratory events were identified in this patient population.…”
Section: Resultsmentioning
confidence: 99%
“…One study that compared the efficacy of IV clonidine or fentanyl in conjunction with ropivacaine given caudally for postoperative pain relief resulted in no significant difference in oxygen saturation (Spo 2 ) (p>0.05). 17 An RCT studied caudal blockade with single dose clonidine, hydromorphone, or morphine combined with ropivacaine with epinephrine in children undergoing ureteral implantation. 18 No postoperative respiratory events were identified in this patient population.…”
Section: Resultsmentioning
confidence: 99%
“…Usha Shukla et al [43] in their study on caudal fentanyl 1 mcg/kg found that mean arterial pressures decreased by 10-15% during anaesthesia and increased by 5-15% during recovery. HR also decreased during anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Minimum cardiotoxicity and a slighter paralysis of motor nerves and muscles dictate the choice of ropivacaine. An alternative to opioids is the addition of 2 µg kg -1 clonidine or 1 µg kg -1 dexmedetomidine [16]. Continuation of local anaesthetic infusion without opioids is advisable prior to planned extubation.…”
Section: Regional Anaesthesiamentioning
confidence: 99%